The selective work with Bahachansky breed type within the Large White pigs - Peresadko L.; Berezovsky M.; Lutsenko M.; Vashhenko P.; Manyunenko S. (Технологія виробництва і переробки продуктів тваринництва, 2021)
The paper deals with Bahachansky type breeding that has been carried out in “Ukraine” farm business, Velyka Bahachka Region, Poltava District. The studies evaluated breeding boars that represent the most numerous interbreed type lines. The breeding boars were evaluated by the quality of the offspring by fattening performance test and estimates based on probit indices. The findings evaluation of the boars according to the fattening and meat qualities of the offspring showed that the descendants of Yola 30581 and Kyuukka 30077 boars had the lowest fat depth (-2.15%, compared to the average level by the groups). At the same time, the offspring of boars Gültor 29997 and Denny 30939 distinguished themselves with the highest live weight at the age of 7 months (+2.4% and +1.92% compared to the average level of the group). It was found that there is a moderate correlation between the signs of fat depth and the average daily gain: -0.31 ± 0.137 (p <0.05). This nature of the correlation will facilitate the breeding, and will provide an opportunity to obtain animals with the largest possible average daily gain and lowest possible fat depth. According to the conducting of breeding work on the fat depth, the variability level was taken into account. It was found that the descendants of Kyuukka 30077 boar had the highest variability level on this basis (higher than the average of the sample by 0.82 percentage points). Evaluation of breeding boars by offspring quality using probit indices showed that the offspring of Gültor 29997 and Denny 30939 boars predominated in terms of live weight at the age of 7 months, in addition, the descendants of Denny 30939 boar were also better in terms of fat depth. It was established that the descendants of Gültor 29997 boar have probably better tenderness of meat in terms of quality. The descendants of Yola 30235 boar are notable for moisture-retaining ability, and the lowest costs of heat treatment were recorded for the descendants of the Tyke 30103 boar. Thus, the quality of meat is significantly affected not only by the level of feeding but also the genotype of the animal.